Swyngedouw's puzzle: Surplus-value production in socionature. Issue 2 (July 2021) - Batubara, Bosman
This article engages with Swyngedouw's puzzle, that is, how is surplus-value production under capitalism conceptualised given the entanglement of humans and non-human entities. It identifies how Swyngedouw's socionature – a concept/way to express the oneness of human and non-human under capitalism – posed a critique to the tendency of labour-centred analysis in Marxist thought such as Neil Smith's concept of 'production of nature' but did not engage with how surplus-value is produced. This article makes visible the role of non-wage-labour in surplus-value production through reference to Moore's concept of value-relations and oikeios .